2001
DOI: 10.1021/jp004262z
|View full text |Cite
|
Sign up to set email alerts
|

How Well Can Hybrid Density Functional Methods Predict Transition State Geometries and Barrier Heights?

Abstract: We compare hybrid Hartree-Fock density-functional theory to ab initio approaches for locating saddle point geometries and calculating barrier heights on a Born-Oppenhiemer potential energy surface. We located reactant, product, and saddle point stationary points for 22 reactions by the MP2 and QCISD ab initio methods and the B3LYP, BH&HLYP, mPW1PW91, and MPW1K hybrid Hartree-Fock DFT methods. We examined all of these methods with two basis sets, 6-31+G(d,p) and MG3. By comparison to calculations on five system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
500
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 575 publications
(533 citation statements)
references
References 36 publications
31
500
2
Order By: Relevance
“…An increase in the exact Hartree-Fock exchange from 0% in pure DFT to 20% in B3LYP to 50% in BHLYP leads to better error cancellation between the reactants and transition states for the computation of barrier heights. 80,82,83 Using restricted orbitals causes most of the DFT barrier heights ∆E ‡ to increase. This significantly improves results for the reaction of H 2 with H, but for the other two symmetric reactions the RBHLYP barriers are overestimated compared to RCCSD(T).…”
Section: Symmetric Reactionsmentioning
confidence: 99%
“…An increase in the exact Hartree-Fock exchange from 0% in pure DFT to 20% in B3LYP to 50% in BHLYP leads to better error cancellation between the reactants and transition states for the computation of barrier heights. 80,82,83 Using restricted orbitals causes most of the DFT barrier heights ∆E ‡ to increase. This significantly improves results for the reaction of H 2 with H, but for the other two symmetric reactions the RBHLYP barriers are overestimated compared to RCCSD(T).…”
Section: Symmetric Reactionsmentioning
confidence: 99%
“…Reaction pathways were investigated using density functional theory (DFT) with Truhlar's (U)M06-2X functional [24,25], in conjunction with a 6-311+G(d,p) basis set. Mardirossian and HeadGordon [26] have recently shown that M06-2X provides good overall performance for reaction thermochemistry.…”
Section: Methodsmentioning
confidence: 99%
“…A number of previous investigations have shown that small aromatic molecules can form via cyclisation of unsaturated hydrocarbons (e.g., 1,3,5-hexatriene [28], hexachloropropene [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]). …”
Section: Reaction Initiationmentioning
confidence: 99%
“…Surface adsorption studies, as well as studies of kinetics and thermochemistry, have been performed extensively using DFT. DFT has its strength in its accuracy and costs compared to other ab initio methods 71,72 . Time and length scales for DFT are in the order of 1 ps to 1 ns and 1 Å to a few nm respectively 73 .…”
Section: Present Status Of Sic-cvd Process Modelingmentioning
confidence: 99%